The mechanism of chloride ion transport in coral concrete by reverse seepage and saturation based active anti corrosion technology (RS-AAT) - Arafat Easin; Jianzhao Ding; Liang Xiao; Guoxiong Mei (Case Studies in Construction Materials)
Chloride-induced corrosion is one of the most critical factors affecting the durability of concrete structures, particularly in marine environments. Coral concrete, widely used in coastal and island construction, is especially vulnerable due to its porous microstructure. This study investigates the chloride ion migration behavior in coral concrete treated with a Reactive Preservation Technique known as Reverse Seepage and Saturation-Based Active Anti-Corrosion Technology (RS-AAT). A combination of experimental testing and numerical simulation was conducted on coral concrete specimens with three different water-to-cement (w/c) ratios over a 120-day exposure period.Results showed that RS-AAT treatment reduced surface chloride ion concentration by over 15 % and decreased total chloride ion content by more than 40 % compared to untreated specimens. Under cyclic wet-dry corrosion conditions, RS-AAT also stabilized chloride concentration gradients, modified the migration pathways, and delayed chloride penetration. These effects were more pronounced in concrete with higher w/c ratios. Furthermore, treated specimens exhibited significantly improved resistance to chloride ingress, confirming the effectiveness of RS-AAT in enhancing the durability of coral concrete.These findings offer valuable insight into the development of sustainable concrete protection methods and contribute to extending the service life of coastal infrastructure exposed to aggressive saline environments.